New The Evolution of Carbon Markets and their Role in Climate Mitigation and Sustainable Development - Bassam Fattouh; Andrea Maino (Oxford Energy Forum: A Quarterly Journal for Debating Energy Issues and Policies, 2022)
Climate science confirms the imperative to maintain global temperatures under 2°C and undertake efforts to limit the rise to 1.5°C above pre-industrial levels in order to avert extreme climate hazards. This requires that global annual greenhouse gas (GHG) emissions are halved by 2030 and reduced to net zero by 2050. Against this background, policymakers have launched initiatives at global and country levels to align socio-economic incentives towards the goals of the Paris Agreement. Among those, carbon markets represent an important element in achieving climate targets by attributing a price to carbon emissions, thus internalizing the climate externality into production and consumption decisions. They also play an important role in enhancing climate ambitions by increasing efficiency gains and lowering the marginal cost of abatement. The importance of these markets has been highlighted recently in the G7 Climate, Energy and Environment Ministers' Communique\' (27 May 2022), which emphasizes 'the crucial potential of carbon markets and carbon pricing for incentivising investments in technologies, infrastructure and Nature-based Solutions that promote a transformation to net zero, accelerate cost-efficient emission reductions, and enhance the alignment of financial flows with the long-term goals of the Paris Agreement', highlighting 'that the revenues generated through carbon markets and carbon pricing can enable countries to finance further climate action, and to support vulnerable and low-income households in the transformation to net zero'. The G7 ministers of climate, energy, and the environment pledged 'to expand the ambitious use of carbon markets and carbon pricing around the world'. Indeed, carbon markets have been expanding rapidly in recent years. According to the Economist3, by the end of 2021 more than 21 per cent of the world's emissions were covered by some form of carbon pricing, with trading on these markets growing by 164 per cent in 2021 to 897 billion. This issue of the Oxford Energy Forum focuses on the role of and recent developments in carbon markets.
Keywords: 330